Postoperative Refractive Prediction Error Measured by Optical and Acoustic Biometry after Phacovitrectomy for Rhegmatogenous Retinal Detachment without Macular Involvement - Masashi Sakamoto; Izumi Yoshida; Takahiro Sodeno; Asao Sakai; Hidetaka Masahara; Takatoshi Maeno (Journal of Ophthalmology)
Introduction. The aim of this study was to investigate the postoperative prediction error measured by optical biometry and acoustic biometry in eyes after phacovitrectomy for rhegmatogenous retinal detachment (RRD) with no macular involvement. Methods. Forty-nine eyes of 49 patients (32 male, 17 female; mean age 62.6 ± 7.5 years) with RRD without macular involvement who underwent phacovitrectomy (RRD group) and 49 eyes of 33 patients (21 male, 12 female; mean age 74.1 ± 7.1 years) without macular disease who underwent cataract surgery (control group) were included in this retrospective comparative study. The difference between the preoperative predictive value and the postoperative refractive value was measured both by optical and acoustic biometry and compared in each group. Results. The postoperative refractive error calculated by acoustic biometry was −0.81 ± 0.75D and that calculated by optic biometry was −0.44 ± 0.77D in the RRD group. The postoperative refractive error calculated by acoustic biometry was −0.21 ± 0.64D and that calculated by optic biometry was 0.27 ± 0.71D in the control group. Significant myopic shifts were observed in the RRD group using both acoustic biometry and optic biometry but not in the control group. Conclusion. Phacovitrectomy for RRD with no macular involvement resulted in a significant myopic shift when compared with cataract surgery alone in patients without macular disease when calculated by both acoustic biometry and optic biometry.